RF CMOS switch design methodologies for multiband transceiver applications - Thangasamy, Veeraiyah; Thiruchelvam, Vinesh; Hashim, Shaiful Jahari; Kamsani, Noor Ain (Universiti Putra Malaysia Press, 2017)
Multimode multiband connectivity has become a de-facto requirement for smartphones with 3G WCDMA/4G LTE applications. In transceivers, multiband operation is achieved by selecting an output from two or more signal path targeting for a specific frequency range in parallel or by using switched capacitor/inductor. In this paper, design methodology of 280nm CMOS switch is presented. Design optimization of RF CMOS switch is presented which is deciding proper selection of CMOS transistor parameters and switch size as per external circuit parameters. The CMOS switch of a 5-transistor stack with W/L=1200µm/280nm provides insertion loss < 0.6dB and isolation loss >14dB. The switches designed when implemented in a multiband power amplifier (PA) exhibits 36dB gain at 1900MHz high-band and 34.5dB gain at 900MHz low-band with 27.5dBm peak power at both bands. The switch design methodologies presented in this paper should be of use in designing various blocks in emerging multiband transceiver applications.